APPLICATION OF COST VOLUME PROFIT ANALYSIS IN PLANNING OF PROFIT - Ika Neni Kristanti (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2014)
Cost volume Profit analysis is a useful tool for planning and decision. Because the Cost Volume Profit analysis emphasizes the linkage between cost, quantity sold, and the price, this analysis in corporates all of the company's financial information. The company's goal in general is to achieve the optimal profit. Profit is a measure that is often used in assessing the success of a company. The key to the success of acompany is measured by the size of the profits received. Planning costs associated with the company's profit, sales volume and selling prices. The objectives to be achieved in this study was to determine how the Cost Volume Profit analysis in decision making and profit planning. In this study, descriptive method is used because the data used in the data of fixed costs and variable costs were obtained from the Company's income statement in January-June 2013. KeywordsCost VolumeProfitAnalysis, Profit Planning